Knoop microhardness test in polymers used for surgical guide manufacturing after the disinfection process - Pereira, Gustavo Macedo; Paulo, Beatriz Cristina de; França, Carolina Gonzales; Conceição, Saulo Pereira; Pereira , Tatiana Cursino; Saavedra, Guilherme de Siqueira Ferreira Anzaloni (Brazilian Dental Science, 2025)
Objective: To analyze the Knoop microhardness of samples made from Dima® Print Guide polymer (Kulzer – Brazil) after different disinfection methods. Material and Methods: A total of 15 samples of the Dima® Print Guide polymer (Kulzer – Brazil) were fabricated and divided into five groups with three samples in each group as follows: 1 - control group (C), in which the samples did not undergo any disinfection method; 2 - disinfected with 2% chlorhexidine (CHX); 3 - disinfected with peracetic acid (PA); 4 - disinfected with 70% alcohol (AL); and 5 - sterilized in an autoclave (AS). Three microindentations were made on the surface of each specimen using a 300 g load for a dwell time of 30 seconds, measured with a microhardness tester model HMV-G21DT (Shimadzu Corporation, Kyoto, Japan). Results: The microhardness results were submitted to one-way ANOVA, which showed statistically significant differences (p